Modelling Youth Basketball Performance Profile in European Championships - Ovidijus Kokanauskas,; Tomas Bietkis,; Jorge Arede,; Nuno Leite, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The current study aims to identify differences in the individual profiles of youth basketball players (U-16, U-18, U-20) as well as to understand if this variation is affected by player-related variables or team final classification. To this end, archival data from 2016-2017 to 2018-2019 (n=1152 game box scores) European youth championships is analysed. First, a discriminant analysis is carried out to examine the individual game-related statistics (mean ± SD). Secondly, after determining the normality of the data, Kruskal-Wallis is performed to compare differences in performance profiles between different age-groups, teams’ final classification and according to players’ position on the court. The resulting findings show significant differences between the playing positions as well as between different age-groups and considering teams’ final standing position. Older age-groups accumulate higher number in field goals scored, field goal percentage, 3-points scored, efficiency and points scored comparing to younger age-group players. Teams’ final classification also has a significant influence on performance profiles of the players. In both cases, the players from the best teams performed better in most of the statistical variables when compared to bottom-4 teams. Results of the present investigation can help coaches differentiate performance indicators of playing positions and predict how it can change throughout age groups. These findings can be used to optimize preparation for individual players and team’s performance.